1998
DOI: 10.1088/0957-0233/9/8/023
|View full text |Cite
|
Sign up to set email alerts
|

Combined compression and shear wave ultrasonic measurements on curing adhesive

Abstract: This paper describes an ultrasonic technique to study the propagation of wide bandwidth compression and shear wave pulses in a curing adhesive. A temperature controlled water filled test cell with transducers placed at either end is used to couple ultrasound into a thin sample of adhesive. A novel sample holder is employed to contain the uncured liquid adhesive between thin polymer films to stop water ingress and a high-precision goniometer is used to align the sample with respect to the transducers. Consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 18 publications
7
42
0
Order By: Relevance
“…These two properties can then be used to determine the density and the adiabatic bulk modulus, b; of the cement. The adiabatic bulk modulus can be written as [16] …”
Section: Acoustic Measurement Principlementioning
confidence: 99%
“…These two properties can then be used to determine the density and the adiabatic bulk modulus, b; of the cement. The adiabatic bulk modulus can be written as [16] …”
Section: Acoustic Measurement Principlementioning
confidence: 99%
“…It has been shown that the speed of bulk waves in the adhesive material, which is dependent primarily on the stiffness of the material, may be used to infer the state of cure of the adhesive [3]. This has motivated studies to monitor curing using ultrasonic techniques [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Combined CW and SW measurements were made on curing adhesive using a goniometer apparatus described elsewhere [7], at temperatures up to 70°C and over frequency bandwidths of I MHz to 16 MHz. The curing adhesive was held in a parallel sided cuvette immersed in a temperature controlled (± 1°C) water bath.…”
Section: Ultrasound Measurementsmentioning
confidence: 99%